Simultaneous sequence transfer into two independent locations of a reporter vector using MultiSite Gateway® Technology - Julie Tubb; Amy C. Groth; Louis Leong; David W. Emery (BioTechniques)
The bacteriophage λ recombination system is increasingly used for recombinant DNA applications that involve the frequent transfer of sequences into and between shuttle and reporter vectors. This approach bypasses the need for restriction endonucleases or ligases and, as such, is easily scalable and automated. However, this system has not yet been tested for the ability to support the simultaneous introduction of donor fragments into two separate target sites of a single reporter plasmid. This attribute would greatly facilitate studies of cis-regulatory elements that only function in specific combinations, such as a class of regulatory elements known as chromatin insulators. With the goal of facilitating a screen for chromatin insulators, we sought to determine whether the commercially available MultiSite Gateway® Technology recombination system could be used to simultaneously insert candidate insulator elements into two separate locations of a functional reporter plasmid. We show that this application is both highly efficient and specific, generating the desired recombination products nearly three quarters of the time without disrupting the specificity of the reporter system. As such, these studies establish a novel application of the MultiSite Gateway Technology for the generation of recombinant reporter plasmids where the constituent elements function in a combinatorial fashion.